Effectiveness of Physical Activity and Android-based SDIDTK Application on Motor Development of Preschool Children - Mailani, Rena; Oktarina, Mona; Bachtiar, Farahdina; Agustiyawan, Agustiyawan; Magdalena, Jun Yanti; Adzani, Ichlasul; Utami, Dyas Laksmita; Nugraha, Ivan Septia; Mulkan, Fathiya Qorrii'aina (Universitas Muhammadiyah Surakarta, 2025)
Introduction: A developmental process always accompanies a child's growth. Children whose growth is good will experience good development as well. Pre-school children begin to be taught activities related to academics, namely recognising letters and numbers, counting, memorising prayers and songs, writing and even reading. These academic abilities must be based on the readiness or maturity of the child's development of gross motor, fine motor, observation, speech and social. To make pre-school children become children who are ready at the next level of education, it is necessary to stimulate proper development by training many children to do physical activities. And to detect children's development, there needs to be an instrument that is fast, easy and precise, one of which is the SDIDTK application based on android. Research objective to determine the effectiveness of physical activity and SDIDTK application based on android on the motor development of PAUD children. Methods: experimental with a total sample of 50 people divided into control and treatment groups. Results: The group that was given physical activity treatment and SDIDTK measurement assistance based on android to parents had better motor development than the control group. Conclusion: physical activity is beneficial for children to improve motor development.